EVALUASI DALAM PEMBELAJARAN - Wahyuningsih, Viandini; Nabila Wibowo , Chairunnisa; Juwita, Melly; Windi Oktara, Tri (PAEDAGOGY : Jurnal Ilmu Pendidikan dan Psikologi, 2025)
Learning evaluation is an essential component of education; however, current practices are still dominated by conventional summative approaches, with limited use of formative, project-based, character-based, and technology-integrated evaluations. This gap indicates a lack of holistic, continuous, and adaptive assessment aligned with 21st-century competencies, particularly in Indonesian primary and lower secondary education. Such conditions require improved evaluation strategies in the Society 5.0 era to ensure more effective and relevant learning. This study employed a library research approach, reviewing 35 articles that met the inclusion criteria—empirical studies or conceptual papers on learning evaluation at the primary and lower secondary levels, published between 2010 and 2024, in Indonesian or English, and sourced from accredited national and international journals. The analysis covered formative, summative, and non-test evaluations (observation, questionnaires, and interviews) using thematic synthesis. The findings reveal that 75% of the articles emphasized summative evaluation, 30% highlighted the implementation of continuous formative assessment, 67% supported project-based evaluation, 60% addressed character-based evaluation, and only 25% discussed the integration of technology in assessment. These results indicate the need for a shift from summative dominance toward integrating formative, project-based, and technology-enhanced evaluation to address instructional weaknesses and optimize curriculum development. Objective, reliable, valid, and continuous evaluation has significant potential to enhance the quality of education and its relevance to future challenges. ABSTRAK Evaluasi pembelajaran merupakan komponen esensial dalam pendidikan, namun praktik di lapangan masih didominasi pendekatan sumatif konvensional dengan penerapan formatif, berbasis proyek, karakter, dan teknologi yang terbatas. Kesenjangan ini menunjukkan minimnya integrasi evaluasi yang holistik, berkelanjutan, dan adaptif terhadap kompetensi abad ke-21, khususnya pada jenjang SD SMP di Indonesia. Kondisi ini menuntut perbaikan strategi evaluasi di era Society 5.0 agar pembelajaran lebih efektif dan relevan. Penelitian ini merupakan library research terhadap 35 artikel yang memenuhi kriteria inklusi, yaitu penelitian empiris atau kajian konseptual tentang evaluasi pembelajaran SD SMP, terbit antara 2010 - 2024, berbahasa Indonesia/Inggris, dan berasal dari jurnal nasional maupun internasional terakreditasi. Analisis mencakup evaluasi formatif, sumatif, dan non-tes (observasi, angket, wawancara) dengan sintesis tematik. Sebanyak 75% artikel menekankan evaluasi sumatif, 30% menggarisbawahi penerapan formatif berkelanjutan, 67% mendukung evaluasi berbasis proyek, 60% mengulas evaluasi berbasis karakter, dan hanya 25% membahas integrasi teknologi evaluasi. Temuan mengindikasikan perlunya pergeseran dari dominasi sumatif menuju integrasi formatif, proyek, dan teknologi, guna memperbaiki kelemahan instruksional dan mengoptimalkan pengembangan kurikulum. Evaluasi yang objektif, reliabel, valid, dan berkesinambungan berpotensi signifikan meningkatkan kualitas pendidikan dan relevansinya terhadap tantangan masa depan.